Syntactic - semantic relationships in mental lexicon with aphasic patients - Sekulić, Martina; Erdeljac, Vlasta; Vargek - Soler, Vesna Maček - Trifunović, Zvjezdana (2006)
The text examines the relative values of the syntactic - semantic relationships in the mental lexicon of aphasic patients.
Projekt MZOS
ENG